The Effect of Collector in Solar Still for Water Productivity Using Runge-Kutta Method - Mardlijah Mardlijah; Achmad Fatoni; Lukman Hanafi (LPPM Institut Teknologi Sepuluh Nopember, 2015)
Solar still is a renewable energy technology. It can reduce crisis of clean and healthy water in some countries. Solar still produces clean and healthy water using the sunlight, but the result of distillate water is not so much. Hence the need for modifications with the addition of collector can increase the yield of distillate water. Mathematical model of solar still with collector is in the form of system of differential equations. It can be solved numerically using Runge-Kutta method. From the simulation, we conclude that the collector increases the amount of distillate water in the solar still.